REDUCING THE RISKS OF ILLICIT TRAFFICKING IN INDUSTRIAL PRODUCTS TO ACHIEVE SUSTAINABLE DEVELOPMENT GOALS - A. L. Lisovsky (Стратегические решения и риск-менеджмент)
Achieving the Sustainable Development Goals is impossible without the active participation of business, including contributing to the environment, improving the quality of human capital, supporting significant initiatives in the field of ensuring economic growth and creating new jobs; ensuring the well-being and health of citizens; ensuring responsible consumption and production. A significant task for achieving the Sustainable Development Goals is the development of mechanisms to protect the domestic market from illegal trafficking of industrial products, which will lead to the protection of public health and increase jobs. And the increase in tax collection will strengthen the social protection of the population.In Russia in 2021, the turnover of counterfeit products amounted to 7.2 billion rubles and, according to experts, will continue to grow. In this regard, it is necessary to analyze the risks of existing mechanisms of protection against counterfeit products and develop measures to reduce them.The object of research in this article is labeling, which is the application of a special DataMatrix code to the packaging and the entry of this unit of goods into the database.The purpose of the article is to develop recommendations on the use of additional visual control tools on the material carriers of the DataMatrix code, protected from forgery, and to assess the probability of the level of risk reduction and the level of possible losses when using them.The novelty of this study was: identification and analysis of risks of possible threats to the security of the mandatory labeling system for various categories of goods; development of a risk register of possible threats to the security of the system with a grouping of qualitatively assessed and quantifiable risks; development and verification of a model for assessing the probability and possible losses for a group of quantifiable risks; assessment of the probability of risks and possible budget losses from non-payment of taxes and excise duties; assessment of the probability of risks and possible losses for a bona fide manufacturer and end user; formation of management measures aimed at reducing the likelihood of risks and reducing the consequences of the potential implementation of risks; assessment of the residual level of probability and exposure to risks when using additional means of visual control on the material carriers of the DataMatrix code; assessment of the residual level of probability and exposure to risks when using additional visual inspection tools on tangible media protected from counterfeiting in similar systems and Track&Trace marking systems implemented in foreign countries.The results obtained can be applied by federal executive authorities in the formation of state policy in the field of increasing the level of security of Russians, significantly reduce the amount of counterfeit and low-quality analogues, effectively combat smuggling, protect legal businesses and consumers, and also allow the state to increase tax collection.